Monetary Policy and the Central Bank in Jordan - Maziad, Samar (IMF Working Papers; Working Paper ;, 2009)
The Central Bank of Jordan (CBJ) and its operational independence changed over time in line with the evolution of the monetary policy framework and as a result of the currency crisis in the late 1980s. The paper examines the developments of the CBJ, its independence in conducting monetary policy and the various instruments at its disposal, with special focus on the certificates of deposit (CDs) market, the main monetary policy instrument, and the treasury bill market. The paper also examines the issue of the autonomy of monetary policy in Jordan given the influence of world interest rates. Although, Jordan operates an exchange rate peg, which has been fixed to the USD since 1995, there is some room for flexibility in operating monetary policy in the short-run, where the CBJ has some autonomy in determining the spread between domestic and US interest rates. VAR and VECM results suggest that the response of the policy rate in Jordan to innovations in the US Federal Fund's rate is less than one-for-one. In the short-run, the CBJ appears to conduct monetary policy in response to domestic inflation and a measure of the domestic output gap.